MAPPING AND IDENTIFYING HALAL PRODUCTS OF MICRO, SMALL, AND MEDIUM ENTERPRISES (MSMEs) IN TERNATE CITY, INDONESIA - Abdul Hadi Sirat; Hartaty Hadady; Mochammad Apriyadi Hadi Sirat; Jaharuddin bin Padli (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2020)
Halal products produced by SMEs in Indonesia have been guaranteed with the birth of Law Number 33 of 2014 concerning Halal Product Guarantee (UUJPH). This study aims to determine and analyze the Mapping and Identification of Halal Products for MSMEs in Ternate City. This research is a case study with a qualitative approach. Data collection methods include interviews and documentation, while the data analysis technique used is descriptive analysis. The results of this study found that MSMEs who registered and received halal label certificates were still relatively small compared to the number of MSMEs in Ternate City. Halal products produced by SMEs in Ternate City are very diverse in number, especially in food and beverage products